Deteksi Logam Berat Merkuri (Hg) pada Air dan Ikan Pasca Pertambangan Emas di Sungai Barito Kabupaten Barito Utara: Detection of Heavy Metal Mercury (Hg) in Water and Fish After Gold Mining in the Barito River, North Barito Regency - Rahmadani Rahmadani; Tuti Alawiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The mining process is sometimes very complex, which can cause damage to the surrounding environment and cause pollution, such as chemical discharge and tailings from the mining process. The waste generated can pollute river water areas such as heavy metals Mercury, Lead, Cadmium, Nickel, and Zinc. To detect metals, an Atomic Absorption Spectroscopy (AAS) instrument is used, which is quite accurate in determining the concentration of metals at very low levels, such as elements of arsenic, antimony, lead, and mercury which can be selectively determined. Based on the qualitative test results, mercury content and levels are 0.141 mg/kg, 0.129 mg/kg, 0.025 mg/kg, 0.130 mg/kg, 0.136 mg/kg, and 0.046 mg/kg. The conclusion based on the results of mercury metal is still safe within the limits of metal contamination.